Um estudo sobre a memória técnica de grupos humanos do holoceno, por meio da variabilidade técnica da cultura material lítica, dos sítios arqueológicos castração e usina localizados em Uruguaiana - RS - Souza, Luana da Silva de (2018)
The present study is part of the work under development in the Memory and Heritage research field, which is linked to the project "Guarda – Rain: Material Culture and Historical and Pre - Historical Societies of the Platinum Basin: research and socialization of knowledge", coordinated by Professor Dr André Luis Ramos Soares, as part of the Post-Graduate Program in History of the Federal University of Santa Maria (PPGH-UFSM), as well as the Post-Graduate Program in Prehistoric Archeology and Rock Art of the Polytechnic Institute of Tomar - Portugal , considering the International Cooperation Agreement established between the Tomar Institute (IPT) and the Federal University of Santa Maria (UFSM), and receives financial support through the CAPES / DS grant. This research consists of the technological analysis of the lithic collection of the Castração and Usina Archaeological Site located in the region of Uruguaiana, southwest of Rio Grande do Sul. The analysis of the lytic material was carried out realized the technological methodology of the French school, seeking to contribute to a greater understanding of the experience of past hunter-gatherer populations and their technical memory. In order to achieve these objectives, the present work has the purpose to identify and understand the operative chain of the lytic collection and its stages, based on a methodology that prioritizes the analysis - from the choices and acquisition of raw material, till the abandonment of object.